Optimization of vector control torque ripple of permanent magnet synchronous motor based on internal model principle. Issue 4 (February 2020) - Ma, Xihe; Lv, Yingjun; Lv, Changzhi; Zhang, Yatong
Abstract: Due to the dead zone effect caused by the non-ideal device of inverter, the currents of the quadrature and straight axis in the synchronous rotation coordinate of permanent magnet synchronous motor (PMSM) contain a large number of harmonic components, resulting in violent torque harmonics. Based on the field weakening control in single current regulator of interior permanent magnet synchronous motor (IPMSM), this paper gives an analysis of the reason for speed fluctuation, and a novel current compensation control strategy based on internal model control is proposed. By this means, the influence of harmonic currents on electromagnetic torque can be reduced meanwhile the advantage of single current regulator in filed weakening control is fully exploited. The feasibility and effectiveness of the proposed scheme are evaluated by Simulation analyses and experimental results.